Interrelatedness between dysbiosis in the gut microbiota due to immunodeficiency and disease penetrance of colitis. Issue 3 (7th September 2015) - Ray, Avijit; Dittel, Bonnie N.
Summary The composition of the microbiome in health and disease has only recently become a major research focus. Although it is clear that an imbalance or dysbiosis in the microbiota is associated with disease, its interrelatedness to disease penetrance is largely unknown. Inflammatory bowel disease (IBD) is an excellent disease in which to explore these questions because of the extensive genetic studies identifying disease susceptibility loci and the ability to easily sample the intestinal microbiota in IBD patients due to the accessibility of stool samples. In addition, mouse models of IBD have contributed to our understanding of the interrelatedness of the gut microbiota and genes associated with IBD. The power of the mouse studies is that multiple colitis models exist that can be used in combination with genetically modified mice that harbour deficiencies in IBD susceptibility genes. Collectively, these studies revealed that bacterial dysbiosis does occur in human IBD and in mouse colitis models. In addition, with an emphasis on immune genes, the mouse studies provided evidence that specific immune regulatory proteins associated with IBD influence the gut microbiota in a manner consistent with disease penetrance. In this review, we will discuss studies in both humans and mice that demonstrate the impact of immunodeficiences in interleukin‐10, interleukin‐17, nucleotide‐binding oligomerization domain (NOD) 2, NOD‐like receptor proteins 3 and 6, Toll‐like receptor or IgA have on the interrelatedness between the composition of the gut microbiota and disease penetrance of IBD and its mouse models.